Similarities and differences of lithuanian and western ukrainian folk towels - Kumpikatė, Eglė; Nykorak, Olena; Nenartavičiūtė, Erika; Herus, Ludmyla; Kutsyr, Tetiana; Kozakevych, Olena; Milašienė, Daiva; Rukuižienė, Žaneta (Wydawnictwo Politechniki Łódzkiej, 2022)
Cognition of unique historical-cultural heritage is very important for each country. It not only enables to identify itself as unique unit, but also to separate itself in the context of the world. One of the values of tangible heritage is folk textile, the geographic, folk and historical-political aspects of which decide its uniqueness and distinctiveness.
Keywords: folk towels; weaving technique; pattern; decor; similarities and differences; ręczniki ludowe; technika tkania; wzór; wystrój; podobieństwa i różnice